PROBLEMATIKA WAKTU IHTIYATH DALAM PEMBUATAN JADWAL SHALAT - Putra, Nanda Trisna (Jurisdictie: Jurnal Hukum dan Syariah, 2012)
The purpose of this research is to find the problems in Ihtiyath in determining the pray time and to know the law status of  prayer during the time. The result shows an ambivalent position  between Ihtiyath definition issued by the Ministry of Religious Affairs with its application.  According to the Ministry of Religious Affairs, Ihtiyath is a security way by adding or subtracting the time in order that pray time schedule does not precede the beginning of time, or beyond the end of time and the law status of someone who prays in Ihtiyath time is posing two possibilities. The first possibility, if someone prays one rakaat completely with its sujud while time is essential, on second rakaat comes to Ihtiyath time so this pray is still judged as qadlaan. The second possibility is that, if someone pray incompletely one rakaat with its sujud then Ihtiyath time comes, this pray is judged qadlaan.   Tujuan dari penelitian ini adalah untuk menemukan masalah-masalah dalam Ihtiyath dalam menentuan waktu sholat dan mengetahui status hukum dari orang yang sholat pada waktu ihtiyath. Hasil penelitian menunjukkan bahwa ada posisi ambivalen antara Ihtiyath yang ditentukan oleh Kementerian Agama dengan aplikasinya. Menurut Kementerian Agama, Ihtiyath adalah suatu cara pengaman melalui penambahan atau pengurangan waktu agar waktu sholat tidak mendahuli awal sholat atau diluar dari akhir wktu sholat dan status hukum orang yang sholat pada waktu ihtiyath memiliki dua kemungkinan. Kemungkinan pertama, jika seseorang sholat satu rakaat dilengkapi dengan sujud pada sebelum ikhtiyath dan   pada rakaat kedua ihtiyath masuk, maka sholatnya dihukumi sebagai qadlaan. Kemungkinan kedua, jika seseorang sholat pada rakaat pertama tidak dilengkapi dengan sujud kemudian ikhtiyath masuk, maka sholatnya dihukumi sebagai qadlaan